Mathematical Model of Coastline Changes in the Ujung Pangkah Gresik Using the Polynomial Lagrange Approach - Hendrata Wibisana; Primasari Cahya Wardhani; Novie Handajani (Jambura Journal of Mathematics, 2023)
Ujung Pangkah Gresik is an area where there is an estuary of a vast river, the Bengawan Solo river. This area annually sends sediment loads transported by the Bengawan Solo river to the Ujung Pangkah estuary so that gradually accumulation occurs, which results in changes in the morphology of the coast on the edge of the Ujung Pangkah coast, Gresik. This study seeks to see the side of shoreline changes on the Ujung Pangkah coast for five years. Then take the change model as a mathematical model that can describe the speed of shoreline change per year using the Lagrange polynomial interpolation method for degrees 1, degrees 2, and degrees 3. The results of shoreline changes that occur are obtained by the Lagrangge polynomial algorithm of degree 3 with R2 of 0.3747 which has a better correlation than degree 1 (0.0313) and degree 2 (0.3741). The results of this study obtained a mathematical model with a Lagrange polynomial approach where degree 3 has the best correlation among other models. This study concludes that by using a mathematical model, an overview of the process of change or natural phenomena can be obtained, where the existing model can predict future changes in the existing coastline.